2010
DOI: 10.5345/jkic.2010.10.1.057
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Green Frame(GF) for the Implementation of Low-carbon Emissions & Long-life Housing

Abstract: The bearing wall apartments which occupy the majority of multi-residential apartment buildings built in Korea, are known for having limited architectural plan flexibility, posing challenges in terms of maintenance and remodeling. The economic losses and environmental issues resulting from the reconstruction of bearing wall apartments are now accumulating to the extent that they are becoming a national concern. Multi-residential apartment buildings, which are now the dominant form of residence in Korea, must ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Green Frame is a column-beam structure formed by connecting a composite precast concrete (CPC) beam with a steel connection on the column side (Lim et al 2012). Numerous studies have shown Green Frame, which couples the economic efficiency of concrete with the constructability of steel, to be structurally stable environmentally friendly, and to reduce the embodied CO 2 by approximately 20~30% when compared to existing structural systems (Hong et al 2009(Hong et al , 2010a(Hong et al , 2010b.…”
Section: Background and Purposementioning
confidence: 99%
“…Green Frame is a column-beam structure formed by connecting a composite precast concrete (CPC) beam with a steel connection on the column side (Lim et al 2012). Numerous studies have shown Green Frame, which couples the economic efficiency of concrete with the constructability of steel, to be structurally stable environmentally friendly, and to reduce the embodied CO 2 by approximately 20~30% when compared to existing structural systems (Hong et al 2009(Hong et al , 2010a(Hong et al , 2010b.…”
Section: Background and Purposementioning
confidence: 99%
“…Maintenance and remodeling are difficult for bearing wall type apartment buildings, which represent 50 % of residences in Korea, due to partitioning by the bearing wall [1]. This has frequently led to the unnecessary reconstruction of apartment buildings, which not only wastes expense and labor, but also can result in socially disruptive events, like a sudden rise of real estate prices [2]. To solve this problem, the government has implemented an incentive system that increases the volume and height limit by 20 % if the apartment applies a rahmen structure, which enables easy remodeling and deformation without structural damage.…”
Section: Background and Purposementioning
confidence: 99%
“…Many countries have increased efforts to reduce greenhouse gases. Such efforts have led to the construction of green buildings throughout the world [2][3][4][5]. In Korea, an energy performance score calculated based on the ''Housing Performance Rating System'' is regarded as an unexpected expense when considering apartment sales [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the bearing wall structure lacks unit changeability, a significant amount of dismantling or reinforcing of structures must be performed when a building requires renovation due to deterioration and a change in lifestyle [2]. As a result, most residents would prefer rebuilding to renovation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation